Bending-resistant, high-rubber and wear-resistant antireflection film and preparation method thereof
By using a multi-layer structure of a base layer, a hardened layer, a high refractive index layer and a low refractive index layer in the anti-reflection film, combining modified resin and nanoparticles, the problems of taking into account both optical and mechanical properties in the prior art are solved, and the problem of taking into account both optical and mechanical properties is realized. High-performance bending and wear-resistant anti-reflective film.
Patent Information
- Application Number
- CN202411334816.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-10
AI Technical Summary
The existing anti-reflective films are difficult to take into account excellent optical and mechanical properties, especially in terms of friction resistance, bending resistance and weather resistance. The binding force of the multi-layer structure is insufficient, with low transmittance and reduced wear resistance. .
Using a sequentially stacked substrate layer, hardened layer, high refractive index layer and low refractive index layer structure, the hardened layer uses modified flexible resin and inorganic nanoparticles, and the high refractive index layer and low refractive index layer are photocured and modified. Composite nanoparticles form multi-layer coatings through UV curing technology to improve the binding force and wear resistance of the coating.
Achieves anti-reflective film that is resistant to bending and wear resistance, with excellent anti-fouling, scratch resistance, rubber friction resistance and bending resistance. It has high contact angle of static water, high transmittance, low reflectivity, and dynamic friction coefficient. Low, the number of bends reaches more than 200,000.
Smart Images

Figure CN119286033A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of anti-reflection materials, and in particular to a bending-resistant, high-rubber wear-resistant anti-reflection film and a preparation method thereof. Background Art
[0002] Anti-reflection film is widely used in many fields due to its excellent optical properties. In daily life, anti-reflection film is applied to glasses and lenses, which can significantly improve the transmittance of lenses, reduce the reflection of external light, and make the field of vision clearer; it is applied to camera lenses and mobile phone lenses to reduce the impact on imaging and improve clarity by reducing reflected light; it is applied to optical devices such as flat-panel displays to improve the surface transmittance of the device, enhance image contrast and reduce glare, and significantly improve the user's comfort in outdoor or strong light conditions. At the same time, anti-reflection film is also widely used in industry and photovoltaic markets. With the increase in market demand, especially the widespread application of electronic products, people's requirements for anti-reflection film are also increasing. It must have excellent optical properties, flexibility and bendability, scratch resistance and wear resistance, as well as excellent anti-buffering properties. At the same time, due to the need for touch, more attention is paid to the wear resistance of anti-reflection film to rubber-like objects, as well as performance indicators such as weather resistance.
[0003] According to different manufacturing processes, anti-reflection films can be divided into dry anti-reflection films and wet anti-reflection films. The dry process uses vacuum evaporation or vacuum magnetron sputtering, which requires a very high vacuum environment (pressure less than 10Pa) and has low production efficiency (machine speed 1m / min), so the equipment cost and production cost of dry anti-reflection films are very high, and the product price is very high. Wet anti-reflection film is one of the main products on the market now. It can be coated in a roll-to-roll manner, with low manufacturing cost, relatively simple production equipment and process, high production efficiency, and the cost of the product can be greatly reduced to one-fourth of the dry anti-reflection film. The key technology of wet process anti-reflection film is mainly the study of the refractive index of the coating material. The principle of anti-reflection is that the interface of the film layer with different refractive indices interferes with the light of the corresponding wavelength and prevents the reflection of the light. The thickness of the coating should be determined by the wavelength of the light. In theory, a multilayer anti-reflection film of N layers can prevent the reflectivity of N wavelengths of light. At present, anti-reflection films cannot take into account excellent optical and mechanical properties, such as poor friction resistance, especially rubber friction resistance, bending resistance and weather resistance need to be improved.
[0004] Currently, most common anti-reflection films are multi-layer structures. Among them, the two-layer anti-reflection film generally consists of a hard coating and a low refractive index layer stacked on a surface. The low refractive index layer uses an organic silicon material with a polydimethylsiloxane structure. Although it can effectively prevent dirt, it has poor scratch resistance. At the same time, the anti-reflection performance of only two layers will change within the visible light wavelength range. Some schemes use a four-layer structure, including a hard coating, a medium refractive index layer, a high refractive index layer and a low refractive index layer, which can obtain excellent anti-reflection performance. At the same time, the refractive index of the low refractive layer can be appropriately increased to reduce the difficulty of developing the low refractive layer. However, the bonding force between the multi-layer structure is insufficient, and the adhesion NG phenomenon becomes the main problem. At the same time, the transmittance is low and the wear resistance is reduced. Although many studies have increased the wear resistance by introducing inorganic particles to increase the strength of the coating, it will greatly reduce the resistance to rubber friction and bending performance.
[0005] Therefore, it is necessary to improve the existing technology to provide a more reliable solution. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a bending-resistant, high-rubber wear-resistant anti-reflection film and a preparation method thereof in view of the deficiencies in the above-mentioned prior art.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: In a first aspect of the present invention, a bending-resistant, high-rubber-wear-resistant anti-reflection film is provided, comprising a substrate layer, a hardening layer, a high-refractive-index layer and a low-refractive-index layer stacked in sequence;
[0008] The hardened layer is obtained by coating a hardened layer coating liquid on the substrate layer and then curing the coating liquid. The raw materials for preparing the hardened layer coating liquid include, by weight:
[0009]
[0010] The flexible resin is a flexible vinyl resin prepared by modifying epoxy vinyl ester resin with carbamate.
[0011] Preferably, the flexible resin is prepared by the following method:
[0012] Under nitrogen protection, n-butyl carbamate and catalyst dibutyltin dilaurate are mixed in a solvent, the temperature is raised to 45-55°C, epoxy vinyl resin is added dropwise, and the reaction is carried out at 45-55°C for 3-12 hours. After the reaction is completed, the mixture is concentrated to a solid content of 60-80%, thereby obtaining the flexible resin; wherein the mass ratio of n-butyl carbamate to epoxy vinyl resin is 1:1-1:2, and the amount of catalyst added accounts for 0.01-0.05% of the total mass of n-butyl carbamate and epoxy vinyl resin.
[0013] Preferably, the hardening resin is a polyurethane acrylate having a functionality ≥ 9;
[0014] The modified inorganic nanoparticles in the modified inorganic nanoparticle dispersion are at least one of nano-silicon dioxide particles and nano-titanium oxide particles modified by a silane coupling agent;
[0015] The silane coupling agent is at least one of γ-methacryloxypropyltrimethoxysilane (KH-570), vinyltrimethoxysilane (A171), and vinyltri(β-methoxyethoxy)silane (KH-A172).
[0016] Preferably, the modified inorganic nanoparticles are prepared by the following method:
[0017] The silane coupling agent is added to an acidic aqueous solution with a pH value of 3.5 to 4.5, mixed evenly, and then the pH value is adjusted to 6.7 to 7.2 with alkali, stirred for 15 to 90 minutes, and then at least one of nano-silicon dioxide particles and nano-titanium oxide particles is added to obtain a modified inorganic nanoparticle dispersion with a solid content of 30 to 50%.
[0018] Preferably, the high refractive index layer is obtained by coating a high refractive index layer coating liquid on the hardened layer and then curing the coating liquid, and the raw materials for preparing the high refractive index layer coating liquid include, by weight:
[0019]
[0020] Preferably, the photocurable resin is a polyurethane acrylate with a functionality of 3-6; the first reactive diluent is at least one of a low-functionality aromatic acrylate, pentaerythritol triacrylate, and trimethylolpropane triacrylate;
[0021] The nano oxide particles are nano ZrO 2 、Nano-TiO 2 , nano ZnO, nano Al 2 O 3 At least one of the above, the particle size of the nano oxide particles is 10 to 80 nm.
[0022] Preferably, the low refractive index layer is obtained by coating a low refractive index layer on the high refractive index layer and then curing the coating, and the raw materials for preparing the low refractive index layer coating include, by weight:
[0023]
[0024]
[0025] Preferably, the modified composite nanoparticle dispersion is prepared by the following method:
[0026] S1. dispersing the hollow silica particles in ethanol under ultrasonic conditions to obtain a hollow silica particle dispersion having a solid content of 20-50%;
[0027] S2. Add a 0.5-5% sodium bicarbonate solution to the hollow silica dispersion under stirring, stir for 0.5-2 hours, then add a 0.5-5% water-soluble aluminum salt solution under stirring, and adjust the pH to 8-11 with aqueous ammonia;
[0028] S3, transferring the mixed solution obtained in step S2 to a reactor with a polytetrafluoroethylene substrate, reacting at 70-90° C. for 4-16 hours, washing with deionized water and ethanol alternately after cooling, centrifuging, vacuum drying at 50° C. for 12 hours, and calcining in a tube furnace at 220-280° C. for 2-4 hours to obtain alumina-hollow silica powder;
[0029] S4, adding a silane coupling agent to an acidic aqueous solution with a pH value of 3.5 to 4.5, then adjusting the pH value to 6.7 to 7.2 with an alkali, stirring for 0.5 to 2 hours, and obtaining a dissolved solution; the mass concentration of the silane coupling agent in the dissolved solution is 0.1% to 2%;
[0030] Adding alumina-hollow silica powder to the dissolving solution and stirring evenly to obtain a silane coupling agent-modified alumina-hollow silica dispersion having a solid content of 30-50%;
[0031] S5, using perfluoropentyl carbinol and hexamethylene diisocyanate as raw materials, with a molar ratio of 1:1 to 1:3, reacting at 50-70°C under nitrogen protection for at least 4 hours to obtain a fluorinated isocyanate prepolymer; mixing epoxy acrylate with the fluorinated isocyanate prepolymer, with a molar ratio of 1:1 to 1:2, and then adding dibutyltin dilaurate as a catalyst, reacting at 50-70°C for 3-12 hours to obtain fluorinated epoxy acrylate, wherein the content of the catalyst is 3-5% of the total mass of the epoxy acrylate and the fluorinated isocyanate prepolymer;
[0032] S6. Mix the fluorinated epoxy acrylate and the silane coupling agent-modified alumina-hollow silica dispersion prepared in step S4 in a mass ratio of 2:1, stir at room temperature for 0.5-2h, wash with ethanol, dry, and dissolve in methyl isobutyl ketone to obtain a modified composite nanoparticle dispersion with a solid content of 10-40%.
[0033] Preferably, the acrylic resin is a fluorine-containing multifunctional acrylic resin having a double bond, selected from at least one of 1,2,8,9-tetrakis{(meth)acryloyloxy}-4,4,5,5,6,6-hexafluorononane, 1,2,9,10-tetrakis{(meth)acryloyloxy}-4,4,5,5,6,6,7,7-octafluorodecane, and 1,2,10,11-tetrakis{(meth)acryloyloxy}-4,4,5,5,6,6,7,7,8,8-decafluoroheptane;
[0034] The auxiliary agent is (meth)acrylate having a perfluoropolyether skeleton.
[0035] Preferably, the first photoinitiator, the second photoinitiator and the third photoinitiator are all selected from one or more of 1,1'-(methylenebis-4,1-phenylene)bis[2-hydroxy-2-methyl-1-propanone] (initiator 127), 1-hydroxycyclohexylphenyl ketone (initiator 184), diphenylphosphine oxide (TPO), and 2-hydroxy-2-methyl-1-phenyl-1-propanone (initiator 1173);
[0036] The first solvent, the second solvent and the third solvent are all selected from one or more of methyl isobutyl ketone, butyl acetate, 2-butanone, propylene glycol methyl ether, ethyl acetate and isopropanol.
[0037] Preferably, the hardened layer has a refractive index of 1.44-1.60 and a thickness of 2.0-7.0 μm; the high refractive index layer has a refractive index of 1.62-1.90 and a thickness of 80-140 nm; and the low refractive index layer has a refractive index of 1.25-1.45 and a thickness of 70-130 nm.
[0038] The second aspect of the present invention provides a method for preparing the bending-resistant, high-rubber wear-resistant anti-reflection film as described above, comprising the following steps:
[0039] 1) mixing a hardening resin, a flexible resin, modified inorganic nanoparticles, a first photoinitiator, and a first solvent, and stirring them uniformly to obtain a hardening layer coating solution;
[0040] Apply the hardening layer coating liquid on the substrate layer, dry it and then UV cure it, the energy is 200mJ / cm 2 ~1000mJ / cm 2 , and obtain a hardened layer;
[0041] 2) mixing the photocurable resin, the first active diluent, the nano-oxide particles, the second photoinitiator, and the second solvent, and stirring them uniformly to obtain a high refractive index coating liquid;
[0042] Apply high refractive index coating liquid on the hardened layer, dry it and then UV cure it, energy 200mJ / cm 2 ~1000mJ / cm2 , obtaining a high refractive index layer;
[0043] 3) mixing the acrylic resin, the second active diluent, the modified composite nanoparticle dispersion, the auxiliary agent, the third photoinitiator, and the third solvent, and stirring them uniformly to obtain a low refractive index coating liquid;
[0044] Apply low refractive index coating liquid on high refractive index coating liquid, dry and UV cure, energy 200mJ / cm 2 ~1000mJ / cm 2 , forming a low refractive index layer, and finally obtaining the bending-resistant, high-rubber wear-resistant anti-reflection film.
[0045] The beneficial effects of the present invention are:
[0046] The present invention provides a bending-resistant, high rubber wear-resistant anti-reflection film. The present invention can meet the appearance uniformity, color uniformity and strong bonding force between the three-layer coating by performing optical design, formula design, thickness design, etc. on the multi-layer coating. The anti-reflection film has excellent anti-fouling and scratch-resistant, rubber friction-resistant and bending-resistant properties.
[0047] In the hardening layer coating liquid of the present invention, a flexible vinyl resin is introduced into the hardening resin, and the combination of the "hard segment" and the flexible chain of the resin formula is prepared, which not only satisfies the requirement that the hardening coating has a certain hardness and supports the wear resistance of the anti-reflection film, but also satisfies the requirement that the hardening coating does not crack in a bent state. In addition, the introduction of carbamate in the preparation process of the flexible vinyl resin can improve the compatibility of the resin and maintain good air-drying properties of the resin surface. The introduction of inorganic nanoparticles modified by a silane coupling agent into the resin can effectively improve the wear resistance. At the same time, under the action of the silane coupling agent, the hardening resin and the flexible resin can be more closely cross-linked.
[0048] In the low refractive index coating liquid of the present invention, aluminum oxide-hollow silica particles modified by fluorinated epoxy acrylic resin are introduced, and aluminum oxide is directionally grown on the surface of hollow silica, so that the low refractive index advantage of hollow silica can be fully utilized, and the advantages of high strength and chemical corrosion resistance of aluminum oxide materials can be fully utilized; in addition, the particles are modified with fluorinated epoxy resin under the action of a silane coupling agent, so that the crosslinking density between the particles and the resin is increased, and the influence of particle agglomeration can be reduced; the combination of the two particles and the combination of the composite particles and the fluorinated epoxy acrylic resin can form a delicate concave-convex shape on the surface of the coating, which is suitable for the wear resistance of soft media such as rubber; (methyl) acrylate with a perfluoropolyether skeleton is introduced as an auxiliary agent, and the perfluoropolyether flexible chain segment has better migration ability and is easy to migrate to the coating surface, giving the coating better smoothness to achieve a hydrophobic and oleophobic effect, which can further synergistically optimize the wear resistance.
[0049] In some preferred embodiments, the bending-resistant, high rubber wear-resistant anti-reflection film provided by the present invention can achieve the following performance indicators: static water contact angle ≥110°, transmittance ≥93%, reflectivity <1%, steel wool wear resistance 1000 times (1kg), rubber wear resistance 1000 times (1kg), dynamic friction coefficient <0.1, bending ≥200,000 times. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 It is a schematic structural diagram of the bending-resistant, high-rubber wear-resistant anti-reflection film of the present invention. DETAILED DESCRIPTION
[0051] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0052] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0053] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0054] The present invention provides a bending-resistant, high-rubber wear-resistant anti-reflection film, referring to Figure 1 , comprising a substrate layer, a hardening layer, a high refractive index layer and a low refractive index layer stacked in sequence;
[0055] The hardened layer is obtained by coating a hardened layer coating liquid on the substrate layer and then curing the coating liquid. The raw materials for preparing the hardened layer coating liquid include, by weight:
[0056]
[0057] In a preferred embodiment, the hardening resin is polyurethane acrylate with a functionality ≥ 9; high functionality resins have a high crosslinking density after curing, thereby increasing the hardness of the coating and enhancing its wear resistance.
[0058] In a preferred embodiment, the flexible resin is a flexible vinyl resin prepared by modifying epoxy vinyl ester resin with carbamate; it has both intrachain unsaturation and chain end unsaturation, and compared with conventional epoxy vinyl ester resins, has excellent corrosion resistance, flexibility and good processability. Due to the introduction of carbamate, the compatibility of the resin is improved, and the good air-drying property of the resin surface can be maintained.
[0059] In a preferred embodiment, the flexible resin is prepared by the following method:
[0060] Under nitrogen protection, n-butyl carbamate and catalyst dibutyltin dilaurate are mixed in a solvent, the temperature is raised to 45-55°C, epoxy vinyl resin is added dropwise, and the reaction is carried out at 45-55°C for 3-12 hours. After the reaction is completed, the mixture is concentrated to a solid content of 60-80%, thereby obtaining a flexible resin;
[0061] The mass ratio of n-butyl carbamate to epoxy vinyl resin is 1:1-1:2, and the amount of catalyst added accounts for 0.01-0.05% of the total mass of n-butyl carbamate and epoxy vinyl resin.
[0062] In a preferred embodiment, the modified inorganic nanoparticles in the modified inorganic nanoparticle dispersion are at least one of nano-silicon dioxide particles and nano-titanium oxide particles modified by a silane coupling agent; wherein the diameter of the nanoparticles is in the range of 10-100 nm, and in order to better achieve surface modification, nanoparticles with a diameter of 20-80 nm are more preferred. Introducing inorganic particles into the resin can effectively improve wear resistance, and under the action of the silane coupling agent, it can promote a tighter cross-linking of the hardened resin and the flexible resin, further improving the hardness of the coating.
[0063] The silane coupling agent is at least one of γ-methacryloxypropyltrimethoxysilane (KH-570), vinyltrimethoxysilane (A171), and vinyltri(β-methoxyethoxy)silane (KH-A172).
[0064] In a preferred embodiment, the modified inorganic nanoparticles are prepared by the following method:
[0065] The silane coupling agent is added to an acidic aqueous solution with a pH value of 3.5 to 4.5, mixed evenly, and then the pH value is adjusted to 6.7 to 7.2 with alkali, stirred for 15 to 90 minutes, and then at least one of nano-silicon dioxide particles and nano-titanium oxide particles is added to obtain a modified inorganic nanoparticle dispersion with a solid content of 30 to 50%.
[0066] In a preferred embodiment, the high refractive index layer is obtained by coating a high refractive index layer coating liquid on the hardened layer and then curing the coating liquid. The raw materials for preparing the high refractive index layer coating liquid include, by weight:
[0067]
[0068] In a preferred embodiment, the photocurable resin is a polyurethane acrylate with a functionality of 3-6.
[0069] In a preferred embodiment, the first reactive diluent is at least one of low-functionality aromatic acrylate, pentaerythritol triacrylate, and trimethylolpropane triacrylate.
[0070] In a preferred embodiment, the nano-oxide particles are nano-ZrO 2 、Nano-TiO 2 , nano ZnO, nano Al 2 O 3 At least one of the nano-oxide particles has a particle size of 10 to 80 nm, more preferably 30 to 60 nm.
[0071] In a preferred embodiment, the low refractive index layer is obtained by coating a low refractive index layer on the high refractive index layer and then curing the coating. The raw materials for preparing the low refractive index layer coating include, by weight:
[0072]
[0073] In a preferred embodiment, the acrylic resin is a fluorine-containing multifunctional acrylic resin having a double bond, selected from at least one of 1,2,8,9-tetrakis{(meth)acryloyloxy}-4,4,5,5,6,6-hexafluorononane, 1,2,9,10-tetrakis{(meth)acryloyloxy}-4,4,5,5,6,6,7,7-octafluorodecane, and 1,2,10,11-tetrakis{(meth)acryloyloxy}-4,4,5,5,6,6,7,7,8,8-decafluoroheptane; the fluorine-containing multifunctional acrylic resin having a double bond can form a cross-linked structure, thereby improving the strength and hardness of the coating film obtained by curing the coating liquid, and improving the scratch resistance and wear resistance of the coating film surface.
[0074] In a preferred embodiment, the additive is a (meth)acrylate having a perfluoropolyether skeleton. The perfluoropolyether skeleton has better migration ability and is easy to migrate to the coating surface, giving the coating better slipperiness to achieve a hydrophobic and oleophobic effect, and further synergistically optimizing wear resistance. The additive is generally added in an amount of 0.5-20 parts, which can effectively improve the anti-fouling properties of the coating, enhance hydrophobicity, and help enhance wear resistance.
[0075] In a preferred embodiment, the modified composite nanoparticles in the modified composite nanoparticle dispersion are aluminum oxide-hollow silica particles modified by fluorinated epoxy acrylic resin. By directionally growing aluminum oxide on the surface of hollow silica, the low refractive index advantage of hollow silica is fully utilized, while the high strength and chemical corrosion resistance of aluminum oxide materials are utilized. In addition, the particles are modified with fluorinated epoxy resin under the action of a silane coupling agent to increase the crosslinking density between the particles and the resin, while reducing the impact of particle agglomeration. The combination of the particle sizes of the two particles and the combination of the composite particles and the fluorinated epoxy acrylic resin can form a delicate concave-convex shape on the coating surface, which is suitable for the wear resistance of soft media such as rubber.
[0076] Specifically, the modified composite nanoparticle dispersion is prepared by the following method:
[0077] S1. dispersing the hollow silica particles in ethanol under ultrasonic conditions to obtain a hollow silica particle dispersion having a solid content of 20-50%;
[0078] S2. Add a 0.5-5% sodium bicarbonate solution to the hollow silica dispersion under stirring, stir for 0.5-2 hours, then add a 0.5-5% water-soluble aluminum salt solution under stirring, and adjust the pH to 8-11 with aqueous ammonia;
[0079] S3, transferring the mixed solution obtained in step S2 to a reactor with a polytetrafluoroethylene substrate, reacting at 70-90° C. for 4-16 hours, washing with deionized water and ethanol alternately after cooling, centrifuging, vacuum drying at 50° C. for 12 hours, and calcining in a tube furnace at 220-280° C. for 2-4 hours to obtain alumina-hollow silica powder;
[0080] S4, adding a silane coupling agent to an acidic aqueous solution with a pH value of 3.5 to 4.5, then adjusting the pH value to 6.7 to 7.2 with an alkali, stirring for 0.5 to 2 hours, and obtaining a dissolved solution; the mass concentration of the silane coupling agent in the dissolved solution is 0.1% to 2%;
[0081] Adding alumina-hollow silica powder to the dissolving solution and stirring evenly to obtain a silane coupling agent-modified alumina-hollow silica dispersion having a solid content of 30-50%;
[0082] S5, using perfluoropentyl carbinol and hexamethylene diisocyanate as raw materials, with a molar ratio of 1:1 to 1:3, reacting at 50-70°C under nitrogen protection for at least 4 hours to obtain a fluorinated isocyanate prepolymer; mixing epoxy acrylate with the fluorinated isocyanate prepolymer, with a molar ratio of 1:1 to 1:2, and then adding dibutyltin dilaurate as a catalyst, reacting at 50-70°C for 3-12 hours to obtain fluorinated epoxy acrylate, wherein the content of the catalyst is 3-5% of the total mass of the epoxy acrylate and the fluorinated isocyanate prepolymer;
[0083] S6. Mix the fluorinated epoxy acrylate and the silane coupling agent-modified alumina-hollow silica dispersion prepared in step S4 in a mass ratio of 2:1, stir at room temperature for 0.5-2h, wash with ethanol, dry, and dissolve in methyl isobutyl ketone to obtain a modified composite nanoparticle dispersion with a solid content of 10-40%.
[0084] The diameter of the hollow silica particles is in the range of 10-100 nm. In order to better achieve surface modification and directional growth, hollow silica particles with a diameter of 20-60 nm are more preferred.
[0085] The diameter of the aluminum oxide particles is preferably in the range of 20-90 nm. Too large a particle size will affect the surface smoothness of the coating and deteriorate the wear resistance.
[0086] The silane coupling agent is a double bond-containing silane coupling agent, preferably at least one of γ-methacryloxypropyltrimethoxysilane (KH-570), vinyltrimethoxysilane (A171), and vinyltri(β-methoxyethoxy)silane (KH-A172).
[0087] The fluorinated epoxy acrylic resin is synthesized by a known method, using short fluorinated carbon chain fluoroalcohol as a raw material to obtain fluorinated isocyanate, which is then synthesized with epoxy acrylic resin to synthesize the fluorinated epoxy acrylic resin.
[0088] In a preferred embodiment, the first photoinitiator, the second photoinitiator, and the third photoinitiator are all selected from one or more of 1,1'-(methylenebis-4,1-phenylene)bis[2-hydroxy-2-methyl-1-propanone] (initiator 127), 1-hydroxycyclohexyl phenyl ketone (initiator 184), diphenylphosphine oxide (TPO), and 2-hydroxy-2-methyl-1-phenyl-1-propanone (initiator 1173).
[0089] In a preferred embodiment, the first solvent, the second solvent and the third solvent are all selected from one or more of methyl isobutyl ketone, butyl acetate, 2-butanone, propylene glycol methyl ether, ethyl acetate and isopropanol.
[0090] In a preferred embodiment, the hardened layer has a refractive index of 1.44-1.60 and a thickness of 2.0-7.0 μm; the high refractive index layer has a refractive index of 1.62-1.90 and a thickness of 80-140 nm; and the low refractive index layer has a refractive index of 1.25-1.45 and a thickness of 70-130 nm.
[0091] The present invention also provides a method for preparing the above bending-resistant, high-rubber wear-resistant anti-reflection film, comprising the following steps:
[0092] 1) mixing a hardening resin, a flexible resin, modified inorganic nanoparticles, a first photoinitiator, and a first solvent, and stirring them uniformly to obtain a hardening layer coating solution;
[0093] Apply the hardening layer coating liquid on the substrate layer, dry it and then UV cure it, the energy is 200mJ / cm 2 ~1000mJ / cm 2 , and obtain a hardened layer;
[0094] 2) mixing the photocurable resin, the first active diluent, the nano-oxide particles, the second photoinitiator, and the second solvent, and stirring them uniformly to obtain a high refractive index coating liquid;
[0095] Apply high refractive index coating liquid on the hardened layer, dry it and then UV cure it, energy 200mJ / cm 2 ~1000mJ / cm 2 , obtaining a high refractive index layer;
[0096] 3) mixing the acrylic resin, the second active diluent, the modified composite nanoparticle dispersion, the auxiliary agent, the third photoinitiator, and the third solvent, and stirring them uniformly to obtain a low refractive index coating liquid;
[0097] Apply low refractive index coating liquid on high refractive index coating liquid, dry and UV cure, energy 200mJ / cm 2 ~1000mJ / cm 2 , forming a low refractive index layer, and finally obtaining a bending-resistant, highly rubber-resistant and wear-resistant anti-reflection film.
[0098] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.
[0099] Example 1
[0100] A bending-resistant, high-rubber wear-resistant anti-reflection film, characterized in that it comprises a substrate layer, a hardening layer, a high-refractive index layer and a low-refractive index layer stacked in sequence;
[0101] S1. Preparation of hardened coating
[0102] S1-1. Preparation of flexible resin:
[0103] Under nitrogen protection, n-butyl carbamate and catalyst dibutyltin dilaurate are placed in a round-bottom flask, DMF is used as a solvent, the temperature is raised to 50°C, epoxy vinyl resin is added dropwise to react, the reaction temperature is controlled at 50°C for 6 hours, and a flexible epoxy vinyl resin is obtained, wherein the mass ratio of n-butyl carbamate to epoxy vinyl resin is 1:1.5, the amount of catalyst added is 0.025wt%, and after the reaction, the flexible resin with a solid content of 70% is obtained by concentration;
[0104] Among them, n-butyl carbamate is produced by Sartomer; dibutyltin dilaurate is produced by McLean; epoxy vinyl resin, MFE-2, is produced by Huachang Polymer.
[0105] S1-2, preparation of modified inorganic nanoparticle dispersion:
[0106] A silane coupling agent γ-methacryloxypropyltrimethoxysilane (KH-570, mass concentration of 0.5%) is added to a weakly acidic aqueous solution (acetic acid aqueous solution) with a pH value of 4, mixed evenly, and then the pH value is adjusted to 7 with an alkali (specifically ammonia water), stirred for 60 minutes, and titanium dioxide particles are added to obtain a modified inorganic nanoparticle dispersion with a solid content of 40%;
[0107] The titanium dioxide particles have a particle size of 100 nm, RTTMIBK15WT%-N24, and are produced by Tokyo Chemical Industry Co., Ltd.
[0108] S1-3, preparation of hardening layer coating liquid:
[0109] 60 parts of hardening resin polyurethane acrylate (functionality 9), 20 parts of the above-mentioned flexible resin, and 3 parts of initiator (127) are weighed in parts by weight, and 60 parts of solvent methyl isobutyl ketone are added and stirred well, and then 10 parts of modified inorganic nanoparticle dispersion are added and stirred well to obtain a hardening layer coating liquid with a solid content of 35%;
[0110] S1-4. Apply the hardening layer coating liquid evenly on the substrate layer (PET substrate), bake in five ovens at 50℃, 60℃, 70℃, 80℃ and 90℃ for a total time of 5 minutes (1 minute in each oven), and cure under ultraviolet light with an energy of 300mJ / cm2 to obtain a hardened layer with a refractive index of 1.55 and a thickness of 5.0μm.
[0111] Among them, polyurethane acrylate, 6199, is produced by Changxing; PET substrate, thickness 75μm, U-403, is produced by Toray.
[0112] S2. Preparation of high refractive index layer
[0113] S2-1. Preparation of high refractive index coating solution
[0114] According to weight, 70 parts of photocurable resin polyurethane acrylate, 5 parts of active diluent pentaerythritol triacrylate, and 3 parts of photoinitiator (127) are weighed in sequence, 100 parts of solvent methyl isobutyl ketone are added and stirred evenly, and then 20 parts of nano oxide zirconium oxide particles are added and stirred evenly to obtain a high refractive index coating liquid with a solid content of 15%.
[0115] S2-2, evenly apply the high refractive index coating liquid on the hardened coating, bake in five ovens at 40℃, 50℃, 60℃, 70℃, and 90℃ for 5 minutes at an energy of 400mJ / cm 2 The film was cured under ultraviolet light to obtain a high refractive index layer with a refractive index of 1.68 and a thickness of 80 nm.
[0116] Among them, the photocurable resin: UV-7600B, produced by Japan Synthetic Chemical Industry Co., Ltd.; pentaerythritol triacrylate, SR444 NS, produced by Sartomer; zirconium oxide particles, 30nm, produced by Sinoplas
[0117] S3. Preparation of low refractive index layer
[0118] S3-1. Preparation of modified composite nanoparticle dispersion:
[0119] S3-1-1, dispersing the hollow silica particles in ethanol under ultrasonic conditions to obtain a hollow silica particle dispersion having a solid content of 35%;
[0120] S3-1-2, while stirring, add a 2.5% sodium bicarbonate solution to the hollow silica dispersion, stir for 1 hour, then add a 2.5% water-soluble aluminum salt (specifically aluminum chloride) solution under stirring, and adjust the pH to 9 with ammonia water;
[0121] S3-1-3, transferring the mixed solution obtained in step S3-1-2 to a reactor with a polytetrafluoroethylene substrate, reacting at 80°C for 8 hours, washing with deionized water and ethanol alternately after cooling, centrifuging, vacuum drying at 50°C for 12 hours, and calcining in a tube furnace at 260°C for 3 hours to obtain alumina-hollow silica powder;
[0122] S3-1-4, adding a silane coupling agent (specifically KH-570, with a mass concentration of 2%) to an acidic aqueous solution (acetic acid aqueous solution) with a pH value of 4, and then adjusting the pH value to 7 with an alkali (specifically ammonia water), stirring for 1 hour, and obtaining a dissolved solution; the mass concentration of the silane coupling agent in the dissolved solution is 0.5%;
[0123] Add the alumina-hollow silica powder prepared in step S3-1-3 to the dissolving solution and stir evenly to obtain a silane coupling agent-modified alumina-hollow silica dispersion having a solid content of 40%;
[0124] S3-1-5, using perfluoropentyl carbinol and hexamethylene diisocyanate as raw materials in a molar ratio of 1:2, reacting at 60°C under nitrogen purge conditions for 4 hours to obtain a fluorinated isocyanate prepolymer; mixing epoxy acrylate with the fluorinated isocyanate prepolymer in a molar ratio of 1:1.5, adding dibutyltin dilaurate as a catalyst in an amount of 4% of the total amount of the above two, and reacting at 60°C for 6 hours to obtain fluorinated epoxy acrylate;
[0125] S3-1-6. Mix the fluorinated epoxy acrylate and the silane coupling agent-modified alumina-hollow silica dispersion prepared in step S3-1-4 in a mass ratio of 2:1, stir at room temperature for 1 hour, wash with ethanol, dry, and dissolve in methyl isobutyl ketone to obtain a modified composite nanoparticle dispersion with a solid content of 25%.
[0126] Among them, hollow silica particles with a particle size of 40nm, ELCOM JX-1009SIV, are produced by Nippon Gas Catalyst & Chemicals; perfluoropentyl carbinol and hexamethylene diisocyanate are produced by Sartomer; and epoxy acrylate is produced by Changxing.
[0127] S3-2, preparation of low refractive index coating liquid:
[0128] Weigh 60 parts of acrylic resin 1,6-bis{(methyl))acryloyloxy}-2,2,3,3,4,4,5,5-octafluorohexane, 5 parts of active diluent pentaerythritol triacrylate, and 5 parts of initiator (127) in sequence, add 90 parts of solvent methyl isobutyl ketone and stir well, then add 30 parts of the modified composite nanoparticle dispersion prepared in step S3-1, add 5 parts of auxiliary agent, stir well to obtain a low refractive index coating liquid.
[0129] S3-3, evenly apply the low refractive index coating liquid on the high refractive index coating, at an energy of 400mJ / cm 2 The film is cured under ultraviolet light to obtain a low refractive index layer with a refractive index of 1.40 and a thickness of 80 nm, and finally a bending-resistant, high rubber wear-resistant anti-reflection film is obtained.
[0130] Among them, 1,6-bis{(methyl))acryloyloxy}-2,2,3,3,4,4,5,5-octafluorohexane is produced by Shanghai Aladdin; pentaerythritol triacrylate, SR444 NS, is produced by Sartomer; and the additive, Fluere UV-370, is produced by China Fluoro Technology.
[0131] The difference between other embodiments and comparative examples and embodiment 1 is that the formulation components are different, and the coating preparation processes are the same. The specific summary is shown in the following Tables 1 and 2, where the component units are all parts by weight.
[0132] Table 1
[0133]
[0134]
[0135] Table 2
[0136]
[0137] In Comparative Example 7, a hollow silica particle dispersion with the same solid content is used to replace the modified composite nanoparticle dispersion in Example 1. The hollow silica particles used to prepare the dispersion are the same as those in Example 1, and the solvent used is also the same.
[0138] The products prepared in Examples 1-7 and Comparative Examples 1-7 were subjected to the following performance tests:
[0139] Adhesion: Use a 100-grid knife to make 100 grids and stick them together with 3M600 tape to see if the coating falls off. If it does not fall off, it is recorded as 5B.
[0140] Static water contact angle: Read the angle within 6 seconds after dropping liquid;
[0141] Steel wool wear-resistant: Steel wool model (#0000), size 2cm*2cm, stroke 4cm, speed 40-60 times / minute, load 1kg;
[0142] Rubber friction: Model: Korean minoan, stroke 4cm, speed 40-60 times / min, load 1kg;
[0143] Transmittance: measured using a spectrophotometer 752N and an "8-degree specular reflection accessory";
[0144] Bending: bending machine;
[0145] Dynamic friction coefficient: 2*2 balance paper is glued to the glass surface with double-sided tape, and AF glass is used for calibration and replacement of balance paper; 200g load, speed 100mm / min, range 50mm.
[0146] The test results are shown in Tables 3 and 4 below:
[0147] Table 3
[0148] Performance Indicators Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Adhesion 5B 5B 5B 5B 5B 5B 5B Water contact angle / ° 112 111 112 110 112 111 112 Steel wool (1kg) ≥1000 ≥1000 ≥1000 ≥1000 ≥1000 ≥1000 ≥1000 Rubber wear-resistant (1kg) ≥1000 ≥1000 ≥1000 ≥1000 ≥1000 ≥1000 ≥1000 Reflectivity(%) 0.78 0.65 0.85 0.55 0.64 0.82 0.77 Bending (200,000 times) OK OK OK OK OK OK OK Transmittance (%) 94.2 93.5 94.5 93.6 93.3 94.0 93.5 Dynamic friction coefficient 0.09 0.10 0.11 0.09 0.08 0.12 0.09
[0149] Table 4
[0150]
[0151]
[0152] According to the above test results, Comparative Example 1 shows that the thickness of the hardened layer is too thin, and the wear resistance of the finished product is seriously reduced; Comparative Examples 2 and 3 show that too high curing energy of the high refractive index layer and too low curing energy of the low refractive index layer will lead to NG adhesion of the finished product; Comparative Example 4 shows that the reduction in the amount of flexible resin in the hardened layer will lead to a decrease in bending performance and weakened rubber resistance; Comparative Example 5 shows that in the low refractive index coating, if no additives are added, the water drop angle of the finished product will decrease, the smoothness will decrease, and the wear resistance will be NG; Comparative Example 6 shows that too few modified composite nanoparticles will lead to poor wear resistance of the rubber, and when hollow particles are added alone without modification (Comparative Example 7), the wear resistance is very poor.
[0153] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A bending-resistant, high-rubber wear-resistant anti-reflection film, characterized in that: It includes a base material layer, a hardening layer, a high refractive index layer and a low refractive index layer stacked in sequence; The hardened layer is obtained by coating a hardened layer coating liquid on the substrate layer and then curing the coating liquid. The raw materials for preparing the hardened layer coating liquid include, by weight: The flexible resin is a flexible vinyl resin prepared by modifying epoxy vinyl ester resin with carbamate.
2. The bending-resistant, high-rubber wear-resistant anti-reflection film according to claim 1, characterized in that: The flexible resin is prepared by the following method: Under nitrogen protection, n-butyl carbamate and catalyst dibutyltin dilaurate are mixed in a solvent, the temperature is raised to 45-55°C, epoxy vinyl resin is added dropwise, and the reaction is carried out at 45-55°C for 3-12 hours. After the reaction is completed, the mixture is concentrated to a solid content of 60-80%, thereby obtaining the flexible resin; wherein the mass ratio of n-butyl carbamate to epoxy vinyl resin is 1:1-1:2, and the amount of catalyst added accounts for 0.01-0.05% of the total mass of n-butyl carbamate and epoxy vinyl resin.
3. The bending-resistant, high-rubber wear-resistant anti-reflection film according to claim 1, characterized in that: The hardening resin is a polyurethane acrylate with a functionality ≥ 9; The modified inorganic nanoparticles in the modified inorganic nanoparticle dispersion are at least one of nano-silicon dioxide particles and nano-titanium oxide particles modified by a silane coupling agent; The silane coupling agent is at least one of γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane and vinyltri(β-methoxyethoxy)silane.
4. The bending-resistant, high-rubber wear-resistant anti-reflection film according to claim 3, characterized in that: The modified inorganic nanoparticles are prepared by the following method: The silane coupling agent is added to an acidic aqueous solution with a pH value of 3.5 to 4.5, mixed evenly, and then the pH value is adjusted to 6.7 to 7.2 with alkali, stirred for 15 to 90 minutes, and then at least one of nano-silicon dioxide particles and nano-titanium oxide particles is added to obtain a modified inorganic nanoparticle dispersion with a solid content of 30 to 50%.
5. The bending-resistant, high-rubber wear-resistant anti-reflection film according to claim 1, characterized in that: The high refractive index layer is obtained by coating a high refractive index layer coating liquid on the hardened layer and then curing the coating liquid. The raw materials for preparing the high refractive index layer coating liquid include, by weight:
6. The bending-resistant, high-rubber wear-resistant anti-reflection film according to claim 5, characterized in that: The photocurable resin is a polyurethane acrylate with a functionality of 3-6; the first reactive diluent is at least one of a low-functionality aromatic acrylate, pentaerythritol triacrylate, and trimethylolpropane triacrylate; The nano-oxide particles are at least one of nano-ZrO2, nano-TiO2, nano-ZnO, and nano-Al2O3, and the particle size of the nano-oxide particles is 10 to 80 nm.
7. The bending-resistant, high-rubber wear-resistant anti-reflection film according to claim 5, characterized in that: The low refractive index layer is obtained by coating a low refractive index layer on the high refractive index layer and then curing the coating. The raw materials for preparing the low refractive index layer coating include, by weight:
8. The bending-resistant, high-rubber wear-resistant anti-reflection film according to claim 7, characterized in that: The modified composite nanoparticle dispersion is prepared by the following method: S1. dispersing the hollow silica particles in ethanol under ultrasonic conditions to obtain a hollow silica particle dispersion having a solid content of 20-50%; S2. Add a 0.5-5% sodium bicarbonate solution to the hollow silica dispersion under stirring, stir for 0.5-2 hours, then add a 0.5-5% water-soluble aluminum salt solution under stirring, and adjust the pH to 8-11 with aqueous ammonia; S3, transferring the mixed solution obtained in step S2 to a reactor with a polytetrafluoroethylene substrate, reacting at 70-90° C. for 4-16 hours, washing with deionized water and ethanol alternately after cooling, centrifuging, vacuum drying at 50° C. for 12 hours, and calcining in a tube furnace at 220-280° C. for 2-4 hours to obtain alumina-hollow silica powder; S4, adding a silane coupling agent to an acidic aqueous solution with a pH value of 3.5 to 4.5, then adjusting the pH value to 6.7 to 7.2 with an alkali, stirring for 0.5 to 2 hours, and obtaining a dissolved solution; the mass concentration of the silane coupling agent in the dissolved solution is 0.1% to 2%; Adding alumina-hollow silica powder to the dissolving solution and stirring evenly to obtain a silane coupling agent-modified alumina-hollow silica dispersion having a solid content of 30-50%; S5, using perfluoropentyl carbinol and hexamethylene diisocyanate as raw materials, with a molar ratio of 1:1 to 1:3, reacting at 50-70°C under nitrogen protection for at least 4 hours to obtain a fluorinated isocyanate prepolymer; mixing epoxy acrylate with the fluorinated isocyanate prepolymer, with a molar ratio of 1:1 to 1:2, and then adding dibutyltin dilaurate as a catalyst, reacting at 50-70°C for 3-12 hours to obtain fluorinated epoxy acrylate, wherein the content of the catalyst is 3-5% of the total mass of the epoxy acrylate and the fluorinated isocyanate prepolymer; S6. Mix the fluorinated epoxy acrylate and the silane coupling agent-modified alumina-hollow silica dispersion prepared in step S4 in a mass ratio of 2:1, stir at room temperature for 0.5-2h, wash with ethanol, dry, and dissolve in methyl isobutyl ketone to obtain a modified composite nanoparticle dispersion with a solid content of 10-40%.
9. The bending-resistant, high-rubber wear-resistant anti-reflection film according to claim 7, characterized in that: The acrylic resin is a fluorine-containing multifunctional acrylic resin having double bonds, and is selected from at least one of 1,2,8,9-tetrakis{(meth)acryloyloxy}-4,4,5,5,6,6-hexafluorononane, 1,2,9,10-tetrakis{(meth)acryloyloxy}-4,4,5,5,6,6,7,7-octafluorodecane, and 1,2,10,11-tetrakis{(meth)acryloyloxy}-4,4,5,5,6,6,7,7,8,8-decafluoroheptane; The auxiliary agent is (meth)acrylate having a perfluoropolyether skeleton.
10. The bending-resistant, high-rubber wear-resistant anti-reflection film according to claim 7, characterized in that: The first photoinitiator, the second photoinitiator, and the third photoinitiator are all selected from one or more of 1,1'-(methylenebis-4,1-phenylene)bis[2-hydroxy-2-methyl-1-propanone], 1-hydroxycyclohexylphenyl ketone, diphenylphosphine oxide, and 2-hydroxy-2-methyl-1-phenyl-1-propanone; The first solvent, the second solvent and the third solvent are all selected from one or more of methyl isobutyl ketone, butyl acetate, 2-butanone, propylene glycol methyl ether, ethyl acetate and isopropanol.
11. The bending-resistant, high-rubber wear-resistant anti-reflection film according to claim 1, characterized in that: in, The hardened layer has a refractive index of 1.44-1.60 and a thickness of 2.0-7.0 μm; the high refractive index layer has a refractive index of 1.62-1.90 and a thickness of 80-140 nm; the low refractive index layer has a refractive index of 1.25-1.45 and a thickness of 70-130 nm.
12. A method for preparing a bending-resistant, high-rubber wear-resistant anti-reflection film as claimed in any one of claims 1 to 11, characterized in that: The following steps are involved: 1) mixing a hardening resin, a flexible resin, modified inorganic nanoparticles, a first photoinitiator, and a first solvent, and stirring them uniformly to obtain a hardening layer coating solution; Apply the hardening layer coating liquid on the substrate layer, dry it and then UV cure it, the energy is 200mJ / cm 2 ~1000mJ / cm 2 , and obtain a hardened layer; 2) mixing the photocurable resin, the first active diluent, the nano-oxide particles, the second photoinitiator, and the second solvent, and stirring them evenly to obtain a high refractive index coating liquid; Apply high refractive index coating liquid on the hardened layer, dry it and then UV cure it, energy 200mJ / cm 2 ~1000mJ / cm 2 , obtaining a high refractive index layer; 3) mixing the acrylic resin, the second active diluent, the modified composite nanoparticle dispersion, the additive, the third photoinitiator, and the third solvent, and stirring them uniformly to obtain a low refractive index coating liquid; Apply low refractive index coating liquid on high refractive index coating liquid, dry and UV cure, energy 200mJ / cm 2 ~1000mJ / cm 2 , forming a low refractive index layer, and finally obtaining the bending-resistant, high-rubber wear-resistant anti-reflection film.
Citation Information
Cited By
High-strength and high-light-transmittance antireflection film and preparation method thereof
CN120716274A
Composite sheet based on electron beam curing and preparation method thereof
CN122103654A
Composite layered protective film for foldable screen and production process therefor
WO2026189580A1